Object Relation Psychoanalytic Criticism On Selected Works of Tennessee Williams - Shakouri, Shadi (2008)
This study uses the object relation psychoanalytical theory to investigate personality development of the characters in Tennessee Williams’s selected plays The Glass Menagerie, A Streetcar Named Desire and Sweet Bird of Youth. It unveils how the characters relate with their environment and in cases when they fail to do so, how they escape from the anxieties and fears of annihilation. Since the autobiographical style is dominant in Tennessee Williams’s works, this research probes into the Williams’s personal life in order to find out the relations between the playwright’s life and his works. It attempts to clarify and explicate the meaning and effect of Williams’s life experiences, using Melanie Klein’s and D.W. Winnicott’s theory of object relation on his selected works. Tennessee Williams experienced losing loved object in his life, and consequently tried for reparation. He had a sense of dependency and guilt through out his life as evidenced by the way he responded to life’s events and the works he created. This study seeks to depict how life is handled from childhood and how the mother plays crucial role in personality shaping. The research gives the reader a new understanding of personalities and the relationships between the individuals and their environment. Loss and unsuccessful reparation, which result in loneliness, anxiety, mourning, melancholia and also dependency, caused by false self and not good-enough mothering, are the major concepts of object relation theory that this study looks into.